Groundwater modeling of the Aguascalientes Valley aquifer to evaluate the transport of fluoride and arsenic: current state and recommended next steps - Hughes Lomelin, Roxana Nicte Ha; Hernández-Hernández, Mario Alberto; Sanchez Quispe, Sonia Tatiana; Medellín-Azuara, Josué; Morande, J. Andrés; Harmon, Thomas (Frontiers in Water, 2025)
This research report evaluates and proposes strategies to address the ongoing problem of elevated fluoride and arsenic concentrations in the Aguascalientes Valley aquifer (AVA) in Mexico, which serves as the main water supply for almost 1.35 million people and supports over 65,000 hectares of irrigated agriculture. First, we evaluate the AVA’s historical piezometric surface and fluoride and arsenic concentrations. We then develop simplified groundwater flow and transport models to integrate regional hydrogeological and water quality datasets, providing a basis for recommended management interventions. Results indicate mean fluoride concentrations of 2.30 ± 1.43 mg/L (MX fluoride standard = 1.5 mg/L), with higher levels southeast of Aguascalientes City and a positive temporal trend. Arsenic concentrations average 0.0126 ± 0.008 mg/L (MX As standard = 0.01 mg/L), with higher concentrations north of the city and a negative temporal trend. The global average concentration in both cases exceeds the national and international regulatory limits, underscoring the need for immediate action. The piezometric level information was sufficient to reproduce the hydrodynamic behavior of the aquifer reliably, while the transient flow model successfully reproduced the spatial gradient of concentrations. According to the developed mathematical models, water security issues are observed within the AVA, while increasing drawdowns and As and F concentrations. To improve water quality and quantity in the AVA, sustainable practices should be implemented, including potential actions to restore groundwater levels, such as managed aquifer recharge options and nature-based solutions.